Ovine squamous cell carcinoma in peruvian plateau high lands: Report cases - Ruelas Calloapaza, Domingo A. (2017)
Squamous cell carcinoma (SCC) is a malignant neoplastic disease that affects various animal species in many parts of the world causing economic losses of varying degrees. In the Peruvian highlands this disease has not yet been reported, so in the present work a macro and microscopic pathological study of SCC is performed. For this purpose 3 ewes with skin tumor were taken from different parts of the Puno region, these specimens were sacrificed, necropsied and samples of tumor tissue and regional lymph nodes were taken for histopathological study. The studies were done in the Laboratory of Pathology of the Faculty of Veterinary Medicine and Animal Science, UNA Puno. The results were as follows: tumoral lesions with bleeding surface, cauliflower appearance, cut resistant and two of them strongly metastatic in regional lymph nodes were observed in the 3 cases. Microscopic lesions were characterized by the presence of pleomorphic squamous cell cords surrounding, in some cases, corneal "beads"; Mitotic figures, some cells with more than one nucleus, as well as hyperchromatic nuclei were observed. The histopathological findings in the sampled regional lymph nodes revealed lesions similar to findings in ECC in situ. It is concluded that the pathological findings of the three cases correspond to ovine squamous cell carcinoma.